Plant growth-promoting rhizobacteria for orphan legume production: Focus on yield and disease resistance in Bambara groundnut - Olanrewaju, Oluwaseyi Samuel; Babalola, Olubukola Oluranti (Frontiers in Sustainable Food Systems, 2022)
Orphan legumes are now experiencing growing demand due to the constraints on available major food crops. However, due to focus on major food crops, little research has been conducted on orphan legumes compared to major food crops, especially in microbiome application to improve growth and yield. Recent developments have demonstrated the enormous potential of beneficial microbes in growth promotion and resistance to stress and diseases. Hence, the focus of this perspective is to examine the potential of plant growth promoting rhizobacteria (PGPR) to improve bambara groundnut yield and quality. Further insights into the potential use of PGPR as a biological control agent in the crop are discussed. Finally, three PGPR genera commonly associated with plant growth and disease resistance (Bacillus, Pseudomonas, and Streptomyces) were highlighted as case studies for the growth promotion and disease control in BGN production.